PENDAMPINGAN MEDIA IKLAN JASA PIJAT DAN URUT TRADISIONAL DI DESA SALAMJAYA PONDOKSALAM PURWAKARTA - Jalaludin Jalaludin; Hanifah Hanifah; Winda Ramadhona (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) – Sekolah Tinggi Agama Islam (STAI) Pelita Nusa Bandung Barat, 2024)
Salamjaya Village is one of the village expansion areas of 3 villages namely Parakansalam, Salamjaya, and Tanjungsari villages. The impact of the division of the village was that the number of MSMEs and service providers was split, some were in the Parakansalam area only, and some were only in the Tanjungsari area. Among the service providers in Salamjaya Village are Traditional Massage and Massage Services, where Massage and Traditional Massage Services are fairly rare to find in the Salamjaya Village environment. Apart from that, Traditional Massage and Massage Services still use very simple advertising media, namely using writing on A4 paper that is laminated. Furthermore, the location of Traditional Massage and Massage Services is not yet available on Google Maps, so that it will be a bit difficult for millennial and Z generations of consumers, because apart from being located in an alley, consumers of this generation find it easier to ask Google for directions, one of which is Google Maps. Therefore, the purpose of this PKM is to carry out media assistance for advertising traditional massage and massage services in the village of Salamjaya Pondoksalam, Purwakarta. The method used in this PKM is counseling and mentoring. The results of the PKM regarding Media Assistance Advertising Traditional Massage and Massage Services in the Village of Salamjaya Pondoksalam Purwakarta are running well and smoothly, it can be seen that MSMEs Massage and Traditional Massage feel very helped by this PKM program. MSME practitioners of Massage and Traditional Massage can understand the importance of advertising media as a means of increasing the number of visitors/consumers, and increasing income. This PKM supporting activity went well and smoothly, it was seen that all the students, both Salamjaya SDN and Harapan Jaya MDTA, were able to follow the PKM Team's lessons and instructions well, even to the point where they were asked to extend the PKM time, because the PKM team was considered very able to help teaching and learning activities at SDN and MDTA.